Islamic Teacher Development: Constructing Islamic Professional Teachers Based on The Khalifah Concept - Syahraini Tambak; Amril Amril; Desi Sukenti (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
Islamic professional teachers have been researched by educational researchers, but placing the concept of Khalifah as part of teacher professionalism has not been found in more detail. This research is a conceptual-literature type and is analyzed using a content analysis approach. An explored Islamic professional teacher design based on the concept of the Khalifah is illustrated; first, implementing the paradigm that the teacher is the personification of the Khalifah as the representative of Allah SWT on earth to teach humans to manage the universe, serve Allah SWT, and teach morals. Second, the teacher develops the aspect of siyadah that is mastering the knowledge related to the learning process by maximizing the power of the potential of the mind, senses and heart that is bestowed by Allah SWT. Besides that, it is worship with actual moral application in carrying out the teaching profession to provide a brilliant civilization. The learning activities carried out by the teacher are to mobilize all potential students to worship Allah SWT by internalizing Islamic behavior, namely; hikmah (wisdom), syaja'ah (brave), hilmi(polite), iffa (simple), jud (generous), ‘adalah (fair) and mahabbah (love). This research has implications for the theory of